Symptom Prevalence in Patients with Advanced, Incurable Illness in Bangladesh - Doherty, Megan; Khan, Farzana; Biswas, Fazle Noor; Khanom, Marufa; Rahman, Rubayat; Tanvir, Mohammad Munirul Islam; Akter, Farhana; Sarker, Mridul; Ahmad, Nezamuddin (Université d'Ottawa | University of Ottawa, 2017)
Context: There is a signi cant need for palliative care for patients living in low- and middle-income countries. The presence and intensity of physical symptoms is a major factor in uencing the suffering of patients at the end of life. Objectives: The primary aim of this study was to determine the prevalence and characteristics of common physical symptoms experienced by patients with advanced, incurable illness in a developing country. Method: This study used semi-structured interviews in patients with advanced cancer or HIV/AIDS in Bangladesh. Results: Pain was the most common symptom (70.6%) and was frequently reported to be severe (62.6%). Very few patients received strong opioids to treat their pain (13.7%). Other frequent symptoms included loss of appetite (23.5%) and fever (19.9%). The average number of physical symptoms reported was 3 (range: 0–23). The majority of patients rated their most recent symptom (excluding pain) as severe (64.3%), with 35.8% continuing to have severe symptom intensity despite treatment. Conclusions: This study reveals the signi cant burden of symptoms, and the associated suffering for patients living with incurable illness, in a developing country. Very few patients received strong opioids, despite frequently having severe pain. Frequently, the treatments that patients received did not alleviate their symptoms. Palliative care is vital for the relief of suffering for patients with advanced and incurable diseases, especially in low- and middle-income countries where access to curative treatments may be limited and patients often present to medical personnel when their illness is in an advanced stage or incurable.
Keywords: Cancer; pain; HIV/AIDS; symptoms and symptom management